An investigation into the relationship between the corporate culture of South African construction firms and performance - Sidumedi, Kgositsile Samuel (My University, 2010)
Poor capacity, poor quality, low productivity and low profit margins continue to characterize the majority of South African construction firms. These shortcomings are attributable to poor cultural practices that are often associated with construction firms. In an effort to devise strategies intended to improve the performance of South African construction firms, this research report investigates the relationship that exists between the corporate culture and performance of South African construction firms. An in depth literature review that identified the key corporate culture dimensions that are critical for the success of construction firms was undertaken. Literature advocating for the existence of a positive relationship between corporate culture and business performance was also explored. To ascertain the level of importance attached to the various corporate culture dimensions by South African construction firms, a survey was undertaken amongst senior employees of different sized construction firms in the Gauteng region. The survey revealed that the respondents from the different sized firms were largely similar in their level of appreciation of the various corporate culture dimensions. The study found that there is generally a positive relationship that exists between the corporate culture and performance of South African construction firms. The degree or intensity of the relationship is largely dependent on the size of the organization. Small and medium sized construction firms demonstrated greater appreciation of the positive relationship between corporate culture and business performance. To improve the performance of South African construction firms, the study recommends that research and development, innovation, benchmarking and customer orientation be prioritized. The study further recommends for the development and adoption of effective human resources retention strategies, this should be coupled with appropriate mentoring and career development programmes
Keywords: Business performance; Construction firms, South Africa; Corporate culture